2020
DOI: 10.1186/s12887-020-02104-x
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate multilevel analysis of the risk factors associated with anthropometric indices in Iranian mid-adolescents

Abstract: Background: The present study was conducted to jointly assess some specific factors related to body fat measures using a multivariate multilevel analysis in a representative sample of Iranian mid-adolescents. Methods: This study was conducted among 2538 students (1286 boys) aged 14-20 years old, who were randomly selected among 16 public high schools by multi-stage random sampling procedure from all education districts of Shiraz, Iran. Data on demographic characteristics, family history of obesity, physical ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The significant correlation observed between fat intake and subscapular skinfold (r = 0.324, p = 0.05) are likely as subscapula skinfold is a measures of fat reserves in the body. This finding is in agreement with that of Alamolhoda et al [20] who observed similar correlations between dietary fat intake and subscapula skinfold thickness in their study of multivariate multilevel analysis of risk factors associated with anthropometric indices in Iranian adolescents. Protein intake in this study showed positive significant correlation with triceps skinfold thickness (r = 0.358).…”
Section: Relationship Between Energy and Nutrient Intakes With Anthro...supporting
confidence: 93%
“…The significant correlation observed between fat intake and subscapular skinfold (r = 0.324, p = 0.05) are likely as subscapula skinfold is a measures of fat reserves in the body. This finding is in agreement with that of Alamolhoda et al [20] who observed similar correlations between dietary fat intake and subscapula skinfold thickness in their study of multivariate multilevel analysis of risk factors associated with anthropometric indices in Iranian adolescents. Protein intake in this study showed positive significant correlation with triceps skinfold thickness (r = 0.358).…”
Section: Relationship Between Energy and Nutrient Intakes With Anthro...supporting
confidence: 93%
“…It is more logical to account for the relationship between estimates of covariate effects and anthropometric indices using a multivariate logistic regression model [ 49 ]. It is used to simultaneously model several interesting categorical outcomes and analyze how they relate to other factors [ 47 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ICC can be calculated using the formula shown below: where and are the estimated cluster variance (regarding to country) and residual variance, respectively [ 47 , 53 ]. The is defined as: [ 47 , 52 ]. After arranging the data in SPSS 26, the statistical analysis was carried out using R software, VGAM, and the GLMER package.…”
Section: Methodsmentioning
confidence: 99%
“…To take under consideration of the correlation between the anthropometric indicators and the estimates of effects of covariates, multivariate logistic regression model is a more plausible alternative [ 5 ]. This statistical model serve to model more than one categorical outcome of interest at a time and assess their association given that of other covariates [ 5 , 17 ].…”
Section: Methodsmentioning
confidence: 99%